Service Firm Performance Transparency: How, When, and Why Does It Pay Off? - Liu,Y; Eisingerich,AB; Auh,S; Merlo,O; Chun,HEH (Journal of Service Research, 2015)
Calls for increased transparency and reduced information asymmetry between service firms and their customers are getting louder in the marketplace. Yet, it remains unclear what exactly constitutes transparency in the eyes of customers and how, if at all, service firms benefit from it. This research contributes to extant knowledge by articulating the key properties of service firms’ performance transparency and by developing and validating a parsimonious scale to measure it. We show that through a reduction in customer uncertainty, the provision of accessible and objective information about a firm’s service offering is positively associated with customers’ intention to purchase and willingness to pay a price premium for its service. Furthermore, we find that the positive effect of performance transparency is influenced by customers’ perceptions of a firm’s ability to deliver on its service promise. An important managerial implication of the current research is that performance transparency benefits customers by lowering uncertainty, and hence service firms should proactively consider it as a critical measure that helps differentiate their services from competitive offerings, even when customer perceptions of a service firm’s ability are low.